On the enumeration of the combinatorial types of primitive parallelohedra in Ed, 2 ≤d≤ 6. (25th July 2013) - Baburin, Igor A.; Engel, Peter
<x xml:space="preserve">Abstract</x> The cone of positive‐definite quadratic forms is subdivided into subcones of combinatorial types of primitive parallelohedra in Ed, 2 ≤d≤ 6. A new algorithm is described and recent results on the enumeration are given.